Pengaruh Adaptasi Kebijakan Work Family Issue terhadap Absence dan Turnover - Triaryati, Nyoman (Jurnal Widya Manajemen & Akuntansi, 2002)
Change in demography of the work force in American and some countries in Asia, such as, the increase number of working mother has increase the work-family issue in work environment. Although work-family conflict is known as a man and women issue, but this issue is continues to place different responsibilities for working women. The different responsibilities is because of the traditional role of women, who take more responsibilities than man for the domestic matter. Work-family issues forced organizations to adopt some policies in order to solve this issue, such as work-family-friendly policy. Some research acknowledge that organization abilities to adopt this kind of policy influence employee response to their work life such as job stress, job satisfaction/dissatisfaction, absence, and turnover. And all of this response have a direct impact to the organization productivity, performance and profitability, in short and in the long run. It is become clear that organizations have to be serious in handling this issue.